2005
DOI: 10.1101/gad.1247705
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional silencing of a transgene by RNAi in the soma ofC. elegans

Abstract: The silencing of transgene expression at the level of transcription in the soma of Caenorhabditis elegans through an RNAi-dependent pathway has not been previously characterized. Most gene silencing due to RNAi in C. elegans occurs at the post-transcriptional level. We observed transcriptional silencing when worms containing the elt-2ϻgfp/LacZ transgene were fed RNA produced from the commonly used L4440 vector. The transgene and the vector share plasmid backbone sequences. This transgene silencing depends on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
142
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 60 publications
5
142
1
2
Order By: Relevance
“…This prediction is based on the role of rde-4 and zfp-1 genes in our characterized system of transcriptional silencing of a transgene (6), the demonstrated requirement of RDE-4 for production of at least some endo-siRNAs (3,26) and on the predicted nuclear function of the ZFP-1 protein. ZFP-1 is a homolog of mammalian protein AF10, which causes myeloid leukemia when fused to MLL (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This prediction is based on the role of rde-4 and zfp-1 genes in our characterized system of transcriptional silencing of a transgene (6), the demonstrated requirement of RDE-4 for production of at least some endo-siRNAs (3,26) and on the predicted nuclear function of the ZFP-1 protein. ZFP-1 is a homolog of mammalian protein AF10, which causes myeloid leukemia when fused to MLL (27).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found that RNAi pathway genes and lin-35(Rb) synergize in repressing the intestinal cell divisions and in repressing the cyclin E gene (cye-1) expression, likely through cooperative inhibition of cye-1 transcription (7). Two chromatinrelated genes, zfp-1 and gfl-1, promote the RNAi process in C. elegans, either directly or indirectly, they also contribute to RNAi-TGS of a repetitive transgene (6,8,9). Interestingly, both genes were also found to antagonize the repressive function of LIN-35(Rb) (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RNAi-dependent transcriptional silencing has been demonstrated to entail histone modifications, such as H3K9 methylation, in eukaryotes belonging to at least three different supergroups (Table 2). Moreover, siRNA-triggered transcriptional repression occurs in organisms that lack cytosine DNA methylation such as S. pombe and C. elegans (Grishok et al 2005;Martienssen et al 2005;Ponger and Li 2005;Robert et al 2005;Volpe et al 2002) and in organisms with very limited DNA methylation such as T. brucei and D. melanogaster (Kavi et al 2005;Pal-Bhadra et al 2004;Ponger and Li 2005;Shi et al 2004;Ullu et al 2004). In contrast, RNA-directed DNA methylation has, thus far, only been demonstrated in plants and mammals (Kawasaki and Taira 2004;Matzke and Birchler 2005;Morris et al 2004) and the role of DNA methylation in this type of gene silencing is somewhat debatable in mammals (Ting et al 2005;Weinberg et al 2006).…”
Section: Additional (Derived?) Functions Of the Rnai Machinerymentioning
confidence: 99%
“…Dcr-1 is accompanied by different Argonaute proteins, Rde-1 and Alg-1͞2, in the RNAi and miRNA pathways, respectively (6,8). Surprisingly, both RNAi and miRNA pathway genes affect RNAi-induced transcriptional gene silencing (RNAi-TGS) in the soma of C. elegans (9).…”
mentioning
confidence: 99%